“At Last! The Government’s War on Poverty Explained”: The Special Planning Secretariat, the Welfare State, and the Rhetoric of the Poverty in the 1960s - Tough, David (Journal of the Canadian Historical Association / Revue de la Société historique du Canada, 2014)
The Special Planning Secretariat was established in the Privy Council Office of the Canadian federal government in 1965 with a mandate to coordinate and promote initiatives against poverty, and was quickly dubbed Canada’s “war on poverty” department. Originally the brainchild of Prime Minister Lester Pearson’s policy chief Tom Kent, who hoped it would make the government’s ambitious social policy agenda more legible, the Secretariat survived Kent’s resignation and took on a lower-profile role generating material to raise public awareness both of poverty and of government’s various efforts to alleviate it. Working in partnership with voluntary organizations and other government agencies including the National Film Board, the Secretariat pioneered new ways of presenting government activities and representing the poor. Its vision of government, reflected in the Index of Programs for Human Development, was comprehensive, reflecting a strategic approach to the federal bureaucracy that would dominate by the 1970s; its representation of poverty, especially in the film The Things I Cannot Change, was bleak and it isolated the poor from social relations. The Secretariat’s activities, which have been obscured by the memory of the redistributive social programmes introduced in the same era, left a mixed legacy for government action to redress poverty.